1996
DOI: 10.1046/j.1365-2567.1996.d01-661.x
|View full text |Cite
|
Sign up to set email alerts
|

Naive human αβ T cells respond to membrane‐associated components of malaria‐infected erythrocytes by proliferation and production of interferon‐γ

Abstract: Crude extracts of Plasmodium falciparum schizont‐infected erythrocytes (PfSE) induce polyclonal activation of peripheral blood T lymphocytes from naive (malaria unexposed) humans. We demonstrate that the active component of PfSE is membrane bound, soluble in sodium dodecyl sulphate (SDS) and partially heat stable, but distinct from the tumour necrosis factor (TNF)‐inducing, exoantigen‐like activity of schizont extracts. Malaria pigment induces little or no T‐cell activation. The responding cells are predominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…Responses tend to peak after 6 -7 days activation in vitro and the proliferating cells have been identified as either TCR␣␤ ϩ T cells, which respond in a classical MHC-restricted manner to both live and dead parasite Ags, or TCR␥␦ ϩ T cells that respond preferentially to live parasites (23,24); both cell types have also been shown to secrete IFN-␥ (21,23,25). Recently, it has been suggested that live P. falciparum can induce rapid (within 12-24 h) IFN-␥ and TNF-␣ responses (31) and that TCR␥␦ ϩ T cells may contribute to the early IFN-␥ response (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Responses tend to peak after 6 -7 days activation in vitro and the proliferating cells have been identified as either TCR␣␤ ϩ T cells, which respond in a classical MHC-restricted manner to both live and dead parasite Ags, or TCR␥␦ ϩ T cells that respond preferentially to live parasites (23,24); both cell types have also been shown to secrete IFN-␥ (21,23,25). Recently, it has been suggested that live P. falciparum can induce rapid (within 12-24 h) IFN-␥ and TNF-␣ responses (31) and that TCR␥␦ ϩ T cells may contribute to the early IFN-␥ response (32).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the human immune response to malaria, we and others have shown that PBMC from malaria-unexposed donors can produce IFN-␥ in response to stimulation by either live or dead schizont Ags (21)(22)(23)(24). Live parasites induce proliferation of both ␣␤ and ␥␦ TCR ϩ T cells, whereas dead schizont extract activates only TCR␣␤ ϩ T cells (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a Th1-to Th2-like shift in immune responsiveness to chronic exposure to infection. Finally, naive a b T cells from non-imm une humans (the cells which would predom inate in younger persons; see above) produced IFN-g but not IL-4 in response to membrane components of red blood cells infected with P. falciparum (Dick et al, 1996).…”
Section: Chronic Exposurementioning
confidence: 99%
“…T cells on D9 to D18 (PI). Dick et al (1996) revealed that the malaria antigens induced expansion of CD4 ? cells from malaria nonexposed individuals.…”
Section: Discussionmentioning
confidence: 99%